ACHIEVEMENTS OF UZBEKISTAN-FRANCE ARCHAEOLOGICAL EXPEDITIONS - Alisher Yarkulov (Journal Park Publishing, 2023)
The activity of the Uzbek-French archaeological expeditions is briefly described in the article. As a result of wide-ranging research, the study of many monuments has brought new conclusions to science. It has been shown that cooperation with the French is of special importance in the archeology of Uzbekistan.
Keywords: scientific research, Afrosiyob, Koktepa, Bactria, Jarqo'ton, Ayokogitma, Old Termiz, Poykend.